Environmental Disputes Without Protection Of Strict Liability Principles: Again, Law On Job Creation - Kusuma, Lalu Aria Nata (Law and Justice, 2022)
The 1945 Constitution of the Republic of Indonesia in Article 28 H paragraph 1 states that a good and healthy environment is a human right and a constitutional right for every Indonesian citizen. The form of environmental protection is then accommodated, one of which is Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH) through the Strict Liability principle or what is called absolute liability for every party who pollutes and destroys the environment caused by Hazardous and Toxic Materials (B3) and waste of Hazardous and Toxic Materials without the need to prove of the element of fault first. However, after the enactment of Law Number 11 of 2020 concerning Job Creation, absolute liability for perpetrators of environmental destruction was lost because the phrase “without the need to prove of an element of fault” was abolished so that accountability was based on mistakes (liability based on fault). The purpose of this study is to determine the impact of eliminating the principle of strict liability in the settlement of environmental disputes in Indonesia. The research method used is normative legal research using statutory, conceptual, and case approaches. Based on the results of the study, it shows that the abolition of strict liability in the Environmental Protection and Management Law will burden victims in environmental disputes, especially ordinary people, to ask for accountability because of the complexity of proving the element of error in industrial activities that use high technology and are related to Hazardous and Toxic Materials (ultrahazardous activity dan abnormally dangerous).   Keywords: Job Creation, Liability Based on Fault, Environmental Dispute, Strict Liability